Analisis tingkat usability dan kualitas website jurusan teknik industri menggunakan metode SUS (System Usability Scale) dan webqual - Pusponegoro, Luh Wianda; Lahay, Idham Halid; Giu, Jamal Darusalam (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The Industrial Engineering Department is one of the departments at the Faculty of Engineering, Gorontalo State University which uses websites as a medium for delivering information. This website is used to convey information regarding class schedules, list of lecturers attending, information about departments, information about labs, final assignments, alumni and department accreditation. To measure the level of usability and quality of websites, the SUS (System Usability Scale) and WebQual methods are used. Seventy-five students majoring in industrial engineering were respondents in this research by selecting answers using a Likert scale. The calculation result of the average SUS score is 54.9, where the score falls into the grade scale F, Adjective Ratings OK and the Acceptability range is marginal low. The results of WebQual calculations, the correlation value obtained is 1 and the significant value is 0. This means that there is a relationship between user satisfaction and the three dimensions of WebQual. From the SUS score and WebQual value, it shows that the website has very low quality so this research recommends improvements.